A Gender-Wise Comparison of Student’s Attitude Towards Biology at Secondary School Leve - Lubna Shaheen (JSE, 2024)
Abstract Purpose of the study was to get an insight of students (boys and girls) attitude towards Biology. Population of the study was all boys and girls enrolled as science students in public Schools of Kahuta Rawalpindi and systematically selected sample was 120 students. The researcher employed a self-constructed Biology Attitude Test. Attitude was further subdivided into six indicators which were interest toward biology, career in biology field, importance of biology, biology teacher, difficulties faced in biology and laboratory equipment. During assessment of boys and girls attitude towards biology applying t-test it was found that interest towards biology, importance of biology and difficulty in biology got values significant upon 0.05 while other indicators like future career in biology, biology teacher and equipment got non-significant values. So attitude of boys and girls towards biology is different at some indicators but almost indifferent at other indicators. Overall value got against attitude found to be non-significant.